Proceedings of the 6th Workshop on Balto-Slavic Natural Language Processing 2017
DOI: 10.18653/v1/w17-1414
|View full text |Cite
|
Sign up to set email alerts
|

Language-Independent Named Entity Analysis Using Parallel Projection and Rule-Based Disambiguation

Abstract: The 2017 shared task at the BaltoSlavic NLP workshop requires identifying coarse-grained named entities in seven languages, identifying each entity's base form, and clustering name mentions across the multilingual set of documents. The fact that no training data is provided to systems for building supervised classifiers further adds to the complexity. To complete the task we first use publicly available parallel texts to project named entity recognition capability from English to each evaluation language. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The team (code "jhu") attempted all languages available in the Challenge. More details can be found in (Mayfield et al, 2017).…”
Section: Participant Systemsmentioning
confidence: 99%
“…The team (code "jhu") attempted all languages available in the Challenge. More details can be found in (Mayfield et al, 2017).…”
Section: Participant Systemsmentioning
confidence: 99%
“…The baseline system (Piskorski et al . 2017) was based on large gazetteers developed by the JRC, while the only other submission covering all Slavonic languages from JHU (Mayfield, McNamee, and Costello 2017) was based on projection of NER labels via word-aligned parallel corpora, see Table 9, as well as a brief explanation of the projection approach in Section 4.…”
Section: Application Studiesmentioning
confidence: 99%
“…One set of approaches uses parallel corpora for projecting automatic annotations in one language to others, for example, for POS tagging (Das and Petrov 2011), parsing (Täckström, McDonald, and Nivre 2013; Tiedemann 2014) and NER (Mayfield et al . 2017). In the projection approaches, the donor part of a parallel corpus is annotated with an existing tool.…”
Section: Related Studiesmentioning
confidence: 99%
“…The task was somewhat different from the 2019 task in that training data was not provided to participants. Approaches submitted to this task included a model based on parallel projection (Mayfield et al, 2017) and a model with language-specific features trained on found data (Marcińczuk et al, 2017). There has also been follow-up work on this dataset using cross-lingual embeddings (Sharoff, 2018).…”
Section: Related Workmentioning
confidence: 99%